Possible interactions and interferences of copper, chromium, and arsenic during the gasification of contaminated waste wood - Al-Badri, Shurooq Badri; Jiang, Ying; Wagland, Stuart T. (MDPI, 2018)
A considerable proportion (about 64%) of biomass energy is produced from woody biomass (wood and its wastes). However, waste wood (WW) is very often contaminated with metal(loid) elements at concentrations leading to toxicity emissions and damages to facilities during thermal conversion. Therefore, procedures for preventing and/or alleviating the negative impacts of these elements require further development, particularly by providing informative and supportive information regarding the phase transformations of the metal(loid)s during thermal conversion processes. Although it is well known that phase transformation depends on different factors such as elements’ vaporization characteristics, operational conditions, and process configuration; however, the influences of reaction atmosphere composition in terms of interactions and interferences are rarely addressed. In response, since Cu, Cr, and As (CCA-elements) are the most regulated elements in woody biomass, this paper aims to explore the possible interactions and interferences among CCA-elements themselves and with Ca, Na, S, Cl, Fe, and Ni from reaction atmosphere composition perspectives during the gasification of contaminated WW. To do so, thermodynamic equilibrium calculations were performed for Boudouard reaction (BR) and partial combustion reaction (PCR) with temperature ranges of 0–1300 °C and 0–1800 °C, respectively, and both reactions were simulated under pressure conditions of 1, 20, and 40 atm. Refinement of the occurred interactions and interferences reveals that Ni-As interactions generate dominant species As2Ni5 and As8Ni11, which increase the solid–gaseous transformation temperature of As. Moreover, the interactions between Ca and Cr predominantly form C3Cr7; whereas the absence of Ca leads to Cr2Na2O4 causing instability in the Cr phase transformation
Keywords: waste wood; interactions; interferences; partial combustion reaction in gasification; Boudouard reaction in gasification; MTDATA